When do creative people engage in malevolent behaviors? The moderating role of moral reasoning. (February 2022) - Zhao, Jingwen; Xu, Xiaobo; Pang, Weiguo
Abstract: While a general manifestation of creativity contributes to desirable outcomes, creative potential may be utilized to harm individuals, property, processes, and symbols on purpose. This is known as malevolent creativity (MC). The present study explores whether moral reasoning moderates the relationship between creative potential and MC behaviors. Specifically, 270 college students were recruited to complete the Runco Ideational Behavior Scale (i.e., self-reported creative potential), two Alternative Uses Tasks (AUT) (i.e., performance-based general creative potential), one malevolent creative problem-solving task (i.e., performance-based malevolent creative potential), the Defining Issues Test 2 (i.e., moral reasoning), and the three-item Malevolent Creative Behavior Scale (i.e., MC behavior). Except for AUT fluency, all other indicators of creative potential were positively correlated with malevolent creative behavior. Moreover, moral reasoning significantly moderated the links between performance-based general (i.e., AUT fluency and originality) and malevolent (i.e., fluency and originality of MC problem-solving) creative potential and MC behavior, showing a stronger potential-behavior association in low rather than high levels of moral reasoning. These findings are discussed in relation to the social cognitive theory. Based on our findings, intervention programs designed to increase individuals' moral reasoning may be utilized to eliminate the transformation from creative potential to real-life MC behaviors. Highlights: Individuals may utilize their creative potential to cause harm. Creative potential positively correlated with malevolent creative behavior. Moral reasoning moderates the above link. Low moral reasoning shows a stronger potential-behavior association.